Urban planning from scratch : collaboration and participation of stakeholders in the urban transformation of Kiruna - Gebremedhin, Frehiwot (Örebro universitet, Institutionen för humaniora, utbildnings- och samhällsvetenskap, 2018)
The forced movement of people from one place to another due to mining is not a new phenomenon. As the mining becomes more intensive, external consequences arise that forces the displacement of people. In this paper, I will investigate the unique case of Kiruna, Sweden where not only the people but also the whole town is being relocated. This move is being coordinated between the different stakeholders involved but mainly by the municipality and the mining company, Luossavaara- Kiirunavaara Aktiebolag (LKAB), which is also covering most of the cost for the relocation. In this research, I aimed at determining how urban planning from a sustainable development view was conducted from scratch and analyzed the public participation in the relocation. An elite interview, text -based documents along with a SWOT analysis were qualitative methods used in this study. The elite interviews and the development plan demonstrated that Kiruna is planning to build a compact city with mixed land use and public places that are easily accessible. Sherry Arnstein´s ladder was used to study citizen participation where it showed a tokenism participation that includes informing, placation and consultation showing that LKAB is shaping the move. In addition, the SWOT analysis showed that the strength and opportunities of the urban transformation were considerably more as opposed to the weakness and threats. In conclusion, this study can be used as an example for future towns that may be displaced and asses the different problems that may arise due to relocation.